Development of Predictive Models through ML Algorithms for the Computation of the Mechanical Behaviour of RC Structures under Pushover Loading Conditions - Yahiaoui, Asma (My University, 2026)
Develop a large dataset through the use of Reconan FEA and HPC LUMI that will be used to train and test AI algorithms for the development of predictive models. The main objective is to replace the need of performing pushover analyses on RC structures with AL generated predictive models.
Keywords: Reinforced Concrete Structures; Seismic Assessment; Machine Learning; High Performance Computing; Finite Element Method; Large Datasets